Medical tourism by Indian-South Africans to India: An exploratory investigation - Dangor, F.; Hoogendoorn, G.; Moolla, R. (Nicolaus Copernicus University Press, 2015)
Medical tourism is a well-established sector in developing countries, and attracts a significant number of tourists from developed countries. Medical tourism is a strong driver of economic growth, but some argue that this kind of tourism promotes inequality in terms of access to healthcare facilities in both developing and developed countries. Whilst research has been conducted on medical tourists travelling to South Africa, no research has focused on the geography of South Africans travelling abroad for medical tourist activities. This study therefore sought to obtain first-hand information from Indian-South African citizens who have partaken in medical tourism in India. Data was gathered through personal, semi-structured interviews conducted with 54 individuals. It was ascertained that the majority of the individuals interviewed in this study travelled to India primarily for medical treatment, while tourist activities were a secondary objective. A smaller proportion of interviewees travelled to India for vacation, with medical care being a secondary motivation, or an impulse due to the low cost of treatment and convenience. Medical tourism by Indian-South Africans travelling to India highlights various shortfalls in South African medical care, including a lack of treatment availability, a poorer quality of service, medical expertise abroad, and the higher cost incurred locally.
Keywords: India; Indian-South Africans; medical tourism; South Africa